Fuel cell ethylene glycol coolant capture cartridge and use thereof
Patent Information
- Application Number
- CN202611297399.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-27
AI Technical Summary
该类方案对初始电导率降低效果明显,但存在以下不足:第一,高纯混床树脂直接承受原始污染冷却液冲击,Fe、Al、Cu、Zn等金属离子和Na+、Cl-、SO42-等导电离子共同消耗混床容量;第二,高价金属离子和二价过渡金属离子的化学性质不同,单一混床树脂或单一螯合树脂难以兼顾不同价态、不同水解倾向金属离子的高效捕获;第三,普通树脂在高温乙二醇-水体系中可能出现可溶性离子、低分子有机物或胺类析出,导致冷却液电导率异常升高;第四,传统混床树脂到寿命后通常整只滤芯更换,无法实现前端金属离子捕获材料的单独再生,耗材成本较高
1、本发明通过高价金属捕获层和二价过渡金属捕获层的分级设置,实现Fe3+、Al3+、Cr3+与Cu2+、Zn2+、Ni2+、Fe2+等不同类型金属离子的分级捕获,避免单一树脂位点被某一类金属离子快速占据。
Smart Images

Figure CN122992103A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fuel cell coolant technology, and more specifically, to a capture capsule for ethylene glycol coolant in fuel cells and its application. Background Technology
[0002] Hydrogen fuel cell systems require a liquid cooling system to dissipate reaction heat and maintain stable stack temperature during operation. Heavy-duty trucks, logistics vehicles, buses, engineering vehicles, and stationary fuel cell systems typically feature high power output, long operating times, large coolant circulation volumes, and high heat loads. Therefore, their liquid cooling systems require high levels of coolant insulation, conductivity stability, and long-term reliability.
[0003] Fuel cell coolants typically use deionized water, ethylene glycol-water mixtures, or fuel cell-specific low-conductivity coolants. During long-term operation, the coolant may come into contact with metal pipes, heat exchangers, water pumps, joints, seals, stack bipolar plates, and other system components, leading to the continuous precipitation of metal ions such as Fe, Al, Cu, Zn, Ni, and Cr. Simultaneously, carbon powder, graphite particles, and metal oxide particles detached from the stack may also enter the coolant circulation system. Ethylene glycol may also undergo oxidative degradation under conditions of high temperature, oxygen, water, and metal ions, forming organic acid salts and other conductive substances. These contaminants increase the coolant conductivity, affecting the insulation safety and long-term stable operation of the fuel cell system.
[0004] Existing fuel cell deionizers typically employ a high-purity mixed-bed resin composed of strong acid cation exchange resin and strong base anion exchange resin to reduce the conductivity of the coolant through ion exchange. This approach is effective in reducing initial conductivity, but it has the following drawbacks: First, the high-purity mixed-bed resin is directly subjected to the impact of the original contaminated coolant, including metal ions such as Fe, Al, Cu, and Zn, and Na+. + Cl - SO4 2- First, the same conductive ions consume the mixed bed capacity. Second, high-valence metal ions and divalent transition metal ions have different chemical properties, making it difficult for a single mixed bed resin or a single chelating resin to efficiently capture metal ions with different valence states and hydrolysis tendencies. Third, ordinary resins may precipitate soluble ions, low-molecular-weight organic matter, or amines in high-temperature ethylene glycol-water systems, leading to an abnormal increase in the conductivity of the coolant. Fourth, traditional mixed bed resins typically require replacement of the entire filter element after the end of their lifespan, making it impossible to regenerate the front-end metal ion capture material separately, resulting in high consumable costs.
[0005] Existing technologies include solutions that incorporate filter layers, chelating resin layers, or mixed-bed resin layers within the deionizer. However, most of these solutions are still single-stage or simple layered structures, lacking a staged capture design for high-valence metal ions and divalent transition metal ions. They also lack methods for removable and regenerable pre-capture layers and dual lifetime determination based on metal ion load / outlet conductivity. For the high-temperature, long-cycle, and continuous metal ion input conditions of ethylene glycol coolant in heavy-duty truck fuel cells, relying solely on ordinary mixed-bed resin or non-renewable chelating resin layers is insufficient to simultaneously meet the requirements of maintaining low conductivity, low pressure drop, low cost, and long lifespan.
[0006] Therefore, there is an urgent need to develop a regenerable multi-stage cooperative pre-capture core that can be installed on the inlet side of the deionizer. Summary of the Invention
[0007] In view of this, the first aspect of the present invention provides a pre-capture core for ethylene glycol coolant in a fuel cell, the pre-capture core being disposed on the coolant inlet side of a deionizer, the pre-capture core comprising, in sequence along the coolant flow direction, an inlet particle filter-distribution layer, a high-valence metal capture layer, a first microporous partition, a divalent transition metal capture layer, a second microporous partition, and a low-deposition buffer protection layer; The high-valence metal trapping layer comprises a first low-precipitation chelating resin containing at least one phosphonic acid group, an aminophosphonic acid group, or a hydroxamic acid group, for trapping Fe. 3+ Al 3+ Cr 3+ One or more high-valence metal ions; The divalent transition metal trapping layer includes a second low-precipitation chelating resin containing at least one iminodiacetic acid group or aminocarboxylic acid group, used to trap Cu. 2+ Zn 2+ Ni 2+ Fe 2+ One or more divalent transition metal ions.
[0008] The low-precipitation buffer protection layer is disposed after the divalent transition metal trapping layer to reduce the impact of front-end modified resin precipitates, resin fine powder and local ion impacts on the rear-end high-purity mixed bed polishing layer. The pre-capture core can be removed from the deionizer and regenerated for reuse after acid washing, cleaning, and ethylene glycol / water replacement. In a preferred embodiment, the first low-precipitation chelating resin uses macroporous styrene-divinylbenzene resin, chloromethylated styrene-divinylbenzene resin, epoxy macroporous resin, amino-modified macroporous resin or a weakly basic macroporous resin that can be modified twice as a matrix, and introduces at least one phosphonic acid group, aminophosphonic acid group or hydroxamic acid group through phosphonomethylation, hydroxamic acidation or aminophosphono acidation reaction.
[0009] In a preferred embodiment, the second low-precipitation chelating resin uses macroporous styrene-divinylbenzene resin, chloromethylated styrene-divinylbenzene resin, epoxy macroporous resin, amino-modified macroporous resin or a weakly basic macroporous resin that can be modified twice as a matrix, and introduces iminodiacetic acid groups and / or aminocarboxylic acid groups through at least one of grafting with iminodiacetic acid or aminocarboxylic acid.
[0010] It should be understood that after acid washing, ultrapure water washing, ethylene glycol-water replacement, and high-temperature pre-stabilization treatment at 90~105℃, the conductivity of the effluent from the first low-precipitation chelating resin after soaking in 50% ethylene glycol-water at 95℃ for 24 hours is ≤20μS / cm, and the TOC is ≤30mg / L. Similarly, after acid washing, ultrapure water washing, ethylene glycol-water replacement, and high-temperature pre-stabilization treatment at 90~105℃, the conductivity of the effluent from the second low-precipitation chelating resin after soaking in 50% ethylene glycol-water at 95℃ for 24 hours is ≤20μS / cm, and the TOC is ≤30mg / L.
[0011] In a preferred embodiment, the volume ratio of the high-valence metal trapping layer to the divalent transition metal trapping layer is 10:90 to 90:10, preferably 30:70 to 60:40.
[0012] In a preferred embodiment, the inlet particle filter-distribution layer occupies 3 to 15% of the effective volume of the pre-capture core.
[0013] In a preferred embodiment, the high-priced metal trapping layer occupies 20-50% of the effective volume of the front trapping core.
[0014] In a preferred embodiment, the divalent transition metal trapping layer occupies 25-55% of the effective volume of the pre-trapping core.
[0015] In a preferred embodiment, the low-deposition buffer protective layer occupies 5-20% of the effective volume of the pre-capture core.
[0016] In a preferred embodiment, the low-precipitation buffer protective layer comprises at least one of the following: hydrophilic end-capped macroporous resin treated with low precipitation, inert macroporous resin, low-precipitation weak acid resin, low-precipitation weak base resin, PPS support particles, PTFE support particles, and PES support particles.
[0017] In a preferred embodiment, the first microporous partition and the second microporous partition are each independently selected from at least one of PPS microporous partition, PPS support mesh, PTFE support mesh, PEEK microporous partition, and PVDF microporous partition.
[0018] In a preferred embodiment, the pore sizes of the first microporous separator and the second microporous separator are 50~500μm, preferably 150~300μm, respectively; and the porosity is 30~70%, preferably 40~55%, respectively.
[0019] In a preferred embodiment, the front capture core includes a detachable core, a pull-out core, a replaceable inner liner, a recyclable resin pack, a perforated cylindrical resin core, or a pouch resin core.
[0020] A second aspect of the present invention provides a method for preparing a pre-capture core capsule, comprising the following steps: The inlet particle filter-distribution layer, the high-valence metal capture layer, the first microporous partition, the divalent transition metal capture layer, the second microporous partition, and the low precipitation buffer protection layer are sequentially filled into the core capsule shell or core capsule bag. After the filled core capsule is subjected to ethylene glycol-water replacement and high-temperature pre-stabilization treatment at 90~105℃, a regenerable multi-stage synergistic pre-capture core capsule is obtained.
[0021] A third aspect of the present invention provides a method for regenerating a pre-capture core, comprising: Remove the pre-capture core that has reached the metal ion load threshold from the deionizer; The pre-capture core capsule was initially rinsed with a mixture of ethylene glycol and water or ultrapure water. The pre-capture core is acid-washed with 0.1~2.0 mol / L acidic regeneration solution to elute one or more metal ions of Fe, Al, Cu, Zn, Ni and Cr from the pre-capture core. Rinse with ultrapure water until the conductivity of the effluent stabilizes; Displacement was performed using an ethylene glycol / water mixture; After undergoing a high-temperature pre-stabilization treatment at 90~105℃ or a low-precipitation final wash, the pre-capture core is reloaded into the deionizer for use.
[0022] In a preferred embodiment, the acidic regeneration solution is hydrochloric acid, sulfuric acid, nitric acid, citric acid, oxalic acid, acetic acid, or a combination thereof, preferably 0.3~1.0 mol / L hydrochloric acid or 0.5~2.0 wt% citric acid.
[0023] A fourth aspect of the present invention provides a deionizer, the deionizer comprising a housing, a coolant inlet, a coolant outlet, a pre-capture core, and a high-purity mixed-bed polishing layer disposed at the rear end of the pre-capture core; the coolant flows sequentially through the coolant inlet, the regenerable multi-stage synergistic pre-capture core, the high-purity mixed-bed polishing layer, and the coolant outlet along the flow direction.
[0024] In a preferred embodiment, the pre-capture core occupies 15-60% of the effective filling volume inside the deionizer, preferably 25-45%; the high-purity mixed-bed polishing layer occupies 40-85% of the effective filling volume inside the deionizer, preferably 55-75%.
[0025] In a preferred embodiment, the high-purity mixed-bed polishing layer comprises an H-type strong acid cation exchange resin and an OH-type strong base anion exchange resin.
[0026] In a preferred embodiment, the deionizer further includes an outlet high-temperature fine filter layer disposed at the rear end of the high-purity mixed bed polishing layer, wherein the outlet high-temperature fine filter layer is a PPS sintered filter, a PPS fiber felt, a PTFE filter, a PES filter, a glass fiber filter, or a combination thereof.
[0027] In a preferred embodiment, the housing is at least one of PPS, PPS and glass fiber, PPA, PEEK, PA66 and glass fiber, aluminum alloy inner lining insulation layer, or stainless steel inner lining insulation layer.
[0028] In a preferred embodiment, the housing is suitable for an ethylene glycol-water coolant circulation system at -30 to 105°C.
[0029] The deionizer has an initial pressure drop of ≤20 kPa, preferably ≤15 kPa, at a coolant flow rate of 10 LPM; and an outlet coolant conductivity of ≤5 μS / cm, preferably ≤1 μS / cm.
[0030] The fifth aspect of this invention provides a method for determining the lifespan of a fuel cell glycol coolant deionizer, the method comprising at least two of the following: The conductivity of the coolant at the deionizer outlet is detected. When the conductivity of the coolant at the outlet reaches the first threshold, it is determined that the high-purity mixed bed polishing layer at the back end is close to failure. The cumulative elution amount of Fe, Al, Cu, Zn, Ni, and Cr in the pre-capture core regeneration solution or pickling solution is detected. When the cumulative elution amount reaches the second threshold, the pre-capture core is deemed to have met the regeneration conditions. The pressure difference between the inlet and outlet of the deionizer is detected. When the pressure difference between the inlet and outlet reaches the third threshold, it is determined that there is a risk of blockage in the inlet particle filter / flow distribution layer or the pre-capture core. Based on the combined output conductivity, cumulative metal ion load, and inlet / outlet pressure difference, the regeneration cycle of the front capture core and the replacement cycle of the high-purity mixed bed polishing layer at the back end are determined. The first threshold is 2~10 μS / cm, preferably 5 μS / cm; the third threshold is 10~30 kPa, preferably 15~20 kPa. The second threshold is determined based on 50~90% of the theoretical metal capture capacity of the chelating resin in the pre-capture core, or based on the total elution amount of Fe, Al, Cu, Zn, Ni, and Cr reaching 0.5~50 mmol / L of resin.
[0031] A sixth aspect of the present invention provides a fuel cell, the fuel cell comprising the aforementioned coolant or the aforementioned deionizer.
[0032] A seventh aspect of the present invention provides an electrochemical energy conversion device, comprising the aforementioned coolant, deionizer, or fuel cell.
[0033] In this invention, unless otherwise stated, the ethylene glycol coolant includes pure ethylene glycol coolant, ethylene glycol-water mixed coolant, 50% ethylene glycol-water coolant, and low-conductivity ethylene glycol coolant for fuel cells.
[0034] The high-valence metal ions mainly refer to Fe. 3+ Al 3+ Cr 3+ Metal ions in trivalent or higher valence states also include the corresponding metal species existing in the coolant in hydrolyzed, hydroxyl-complexed, or oxide-dissolved states.
[0035] In this invention, the divalent transition metal ion mainly refers to Cu. 2+ Zn 2+ Ni 2+ Fe 2+ Mn 2+ Divalent metal ions.
[0036] In this invention, "low precipitation" means that after the resin, filter material, or core assembly has undergone cleaning, replacement, and high-temperature pre-stabilization treatment, the conductive ions, organic matter, and background metal ions released in the ethylene glycol-water system are within the acceptable range of the fuel cell coolant.
[0037] Compared with the prior art, the present invention has at least the following beneficial effects: 1. This invention achieves Fe by hierarchically setting up a high-valence metal trapping layer and a divalent transition metal trapping layer. 3+ Al 3 + Cr 3+ With Cu 2+ Zn 2+ Ni 2+ Fe 2+ The graded capture of different types of metal ions prevents a single resin site from being rapidly occupied by a particular type of metal ion.
[0038] 2. This invention retains metal ions primarily within the regenerable pre-capture core, allowing the high-purity mixed-bed polishing layer at the rear to primarily undertake low-conductivity polishing tasks, thereby reducing the load on the rear mixed bed and extending the overall service life of the deionizer.
[0039] 3. The pre-capture core of the present invention is detachable, recyclable, and acid-washable for regeneration, which can reduce the consumable costs caused by the scrapping and replacement of the entire deionizer.
[0040] 4. The low precipitation buffer protective layer and high temperature pre-stabilization treatment described in this invention can reduce the risk of secondary contamination of the downstream mixed bed and coolant by the front-end modified resin.
[0041] 5. This invention establishes a lifespan determination method that combines changes in metal ion load, outlet conductivity, and voltage drop. This method can distinguish between the front capture cartridge reaching regeneration conditions, the rear mixed bed reaching replacement conditions, and the risk of filter element blockage, thereby improving maintenance accuracy.
[0042] 6. This invention is applicable to the high-temperature ethylene glycol coolant scenario of heavy-duty truck fuel cells, and can also be extended to other fuel cell vehicles, stationary fuel cell systems, and electrochemical systems using low-conductivity ethylene glycol coolant. Attached Figure Description
[0043] Appendix Figure 1 This is a schematic diagram of the overall structure of the regenerative multi-stage synergistic pre-capture core and deionizer of the present invention.
[0044] Appendix Figure 2 This is a schematic diagram of the multi-level structure distribution inside the front capture core capsule of the present invention.
[0045] Appendix Figure 3 This is a schematic diagram of the hierarchical capture mechanism of the high-valence metal capture layer and the divalent transition metal capture layer of the present invention.
[0046] Appendix Figure 4 This is a schematic diagram of the pre-capture core regeneration process of the present invention.
[0047] Appendix Figure 5 This is the logic diagram for determining the composite lifetime of metal ion load / outlet conductivity / voltage drop in this invention.
[0048] Appendix Figure 6 This is a comparison of the metal ion penetration curves of different deionizer systems for the Fe, Al, Cu, and Zn composite contaminated coolant in the examples.
[0049] Appendix Figure 1 and attached Figure 2In the middle section, 1. Shell; 2. Coolant inlet; 3. Inlet particle filter / flow distribution layer; 4. High-valence metal capture layer; 5. First microporous baffle; 6. Divalent transition metal capture layer; 7. Second microporous baffle; 8. Low precipitation buffer protection layer; 9. Regenerable pre-capture core; 10. High-purity mixed bed polishing layer; 11. Outlet high-temperature fine filtration layer; 12. Coolant outlet; 13. Core shell; 14. Core end cap; 15. Regenerated liquid inlet; 16. Regenerated liquid outlet. Detailed Implementation
[0050] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0051] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0052] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0053] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0054] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0055] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0056] The sources of some components in the embodiments are as follows. These sources are merely examples and do not constitute a limitation on the scope of protection of this invention. In actual production, domestically sourced products with equivalent purity and technical specifications can be used as substitutes.
[0057] Chloromethylated polystyrene-divinylbenzene macroporous resin, epoxy-based macroporous resin, weakly basic macroporous resin, and amino-based macroporous resin can be purchased from Xi'an Lanxiao Technology New Materials Co., Ltd., Zhejiang Zhengguang Industrial Co., Ltd., Jiangsu Suqing Water Treatment Engineering Group Co., Ltd., Nankai University Chemical Plant, or equivalent domestic resin suppliers.
[0058] High-purity mixed-bed resin, strong acid cation exchange resin, strong base anion exchange resin, and polishing-grade mixed-bed resin were purchased from Xi'an Lanxiao Technology New Materials Co., Ltd.
[0059] Phosphorous acid, formaldehyde solution, paraformaldehyde, ethylenediamine, diethylenetriamine, aminotrimethylenephosphonic acid, hydroxylamine hydrochloride, hydroxylamine hydrochloride, iminodiacetic acid, aminotriacetic acid, glycine, ethanolamine, diethanolamine, citric acid, hydrochloric acid, sodium hydroxide, sodium carbonate, ethanol, methanol, N,N-dimethylformamide, dimethyl sulfoxide, ethylene glycol, etc., can be purchased from Sinopharm Chemical Reagent Co., Ltd.
[0060] PPS microporous separators, PPS support mesh, PTFE support mesh, PPS sintered filter sheets, PPS fiber felt, PES filter sheets, glass fiber filter sheets, core shells, core end caps, etc., can be purchased from domestic polymer filter material, membrane, and engineering plastic processing suppliers or processed and prepared by the company; materials that are resistant to ethylene glycol, resistant to 95~100℃, have low precipitation, and are compatible with PPS+GF shells are preferred.
[0061] Example 1: Preparation of a resin for capturing low-precipitation high-valence metals This embodiment provides a method for preparing a low-precipitation phosphonic acid / hydroxyoxime acid composite modified resin for use in high-valence metal trapping layers.
[0062] S1. Resin Matrix Pretreatment. Weigh 1000g of chloromethylated polystyrene-divinylbenzene macroporous resin with a particle size of 0.8mm, a chlorine content of 4.0mmol / g, and a crosslinking degree of 8%. Add it to 5L of ethanol and stir and wash for 2h, then filter; wash three times with deionized water; add 5L of 1.0mol / L hydrochloric acid solution and stir at 25℃ for 4h; filter and wash with deionized water until pH 6.5; then add 5L of 0.5mol / L sodium hydroxide solution and stir for 2h, finally wash with deionized water until neutral to obtain the pretreated resin.
[0063] S2. Resin swelling. The pretreated resin was added to 4L of a mixed solvent of N,N-dimethylformamide and water, with a volume ratio of N,N-dimethylformamide to water of 7:3, and swollen at 50℃ for 8 hours.
[0064] S3. Amination reaction. The swollen resin was added to a 3L mixed solution of ethylenediamine and ethanol (volume ratio of ethylenediamine to ethanol: 1:3) and reacted at 60℃ for 8 hours to convert some chloromethyl sites into amino sites. The mixture was filtered and washed with ethanol and deionized water to obtain the amination resin.
[0065] S4. Phosphine methylation reaction. The amination resin is added to the reaction vessel, along with 400g of phosphorous acid, 320g of 37wt% formaldehyde solution, and 3L of deionized water. The pH is adjusted to 1.5 with hydrochloric acid, and the reaction is carried out at 90℃ for 12h to induce phosphine methylation at the amino sites, introducing aminophosphonic acid sites to obtain phosphonic acid modified resin.
[0066] S5. Hydroxyxamic acidification treatment. Phosphonic acid-modified resin was added to an aqueous solution of hydroxylamine hydrochloride (180 g). The pH was adjusted to 6.5 with sodium hydroxide, and the reaction was carried out at 60°C for 6 hours, converting some esterification or acylation sites in the resin into hydroxyxamic acid sites. After the reaction, the resin was washed with deionized water.
[0067] S6. End-capping and low-precipitation treatment. The obtained resin was added to 3 L of 5 wt% ethanolamine aqueous solution and reacted at 60 °C for 6 h to block residual chloromethyl sites. Subsequently, it was subjected to acid washing with 1.0 mol / L hydrochloric acid, washing with ultrapure water, replacement with 25% ethylene glycol / water, and replacement with 50% ethylene glycol / water, and pre-stabilized at 95 °C in 50% ethylene glycol-water for 48 h to obtain a low-precipitation high-valence metal capturing resin.
[0068] The high-valent metal capturing resin obtained in this embodiment contained 0.92 mmol / g of phosphonic acid groups and 0.28 mmol / g of hydroxamic acid groups. After soaking in 50% ethylene glycol-water at 95°C for 24 hours, the effluent had a conductivity of 9.8 μS / cm and a TOC of 14.2 mg / L. (The last sentence appears to be incomplete and possibly refers to a different example.) 3+ And Al 3+ When performing static adsorption evaluation on mixed solutions, Fe 3+ The equilibrium adsorption capacity was 1.42 mmol / g, Al 3+ The equilibrium adsorption capacity was 1.18 mmol / g.
[0069] Example 2: Preparation of a resin for capturing low-precipitation divalent transition metals This embodiment provides a low-precipitation IDA / aminocarboxylic acid modified resin for use in divalent transition metal trapping layers.
[0070] S1. Resin matrix pretreatment. Weigh 1000g of chloromethylated polystyrene-divinylbenzene macroporous resin with a particle size of 0.6mm, a chlorine content of 4.2mmol / g, and a crosslinking degree of 8%, and pretreat it according to the method in S1 of Example 1.
[0071] S2. Resin swelling. The pretreated resin was added to 4 L of a mixed solvent of N,N-dimethylformamide and water, with a volume ratio of N,N-dimethylformamide to water of 7:3, and swollen at 50°C for 8 h.
[0072] S3. Iminodiacetic acid grafting. Weigh 520 g of iminodiacetic acid and add it to 2 L of deionized water. Slowly add sodium carbonate to adjust the pH to 10, forming a sodium iminodiacetic acid solution. Add this solution to the swollen resin, then add 1 L of N,N-dimethylformamide. React at 75 °C for 16 h to allow the chloromethyl sites to undergo a nucleophilic substitution reaction with the iminodiacetic acid salt.
[0073] S4, Aminocarboxylic acid supplementary grafting. The resin obtained in S3 was added to a mixed solution of sodium glycinate and sodium nitrilotriacetate, with 150 g of glycinate and 120 g of nitrilotriacetate. The pH of the system was 10, and the reaction was carried out at 70℃ for 8 h to introduce supplementary aminocarboxylic acid coordination sites.
[0074] S5. End-capping and low-precipitation treatment. The obtained resin was added to a 5 wt% aqueous ethanolamine solution and reacted at 60 °C for 6 h; then it was sequentially subjected to acid washing with 1.0 mol / L hydrochloric acid, washing with ultrapure water, replacement with 25% ethylene glycol-water, and replacement with 50% ethylene glycol-water, and pre-stabilized at 95 °C in 50% ethylene glycol-water for 48 h to obtain a low-precipitation divalent transition metal capturing resin.
[0075] The iminodiacetic acid group content and aminocarboxylic acid group content in the divalent transition metal capturing resin obtained in this embodiment were 1.46 mmol / g and 0.31 mmol / g, respectively. After soaking at 95°C in 50% ethylene glycol / water for 24 h, the conductivity of the effluent was 8.1 μS / cm and the TOC was 12.8 mg / L. (The last sentence appears to be incomplete and possibly refers to a different example.) 2+ and Zn 2+ When performing static adsorption evaluation on mixed solutions, Cu 2+ The equilibrium adsorption capacity was 1.62 mmol / g, Zn 2+ The equilibrium adsorption capacity was 1.45 mmol / g.
[0076] Example 3: Preparation of Low-Deposition Buffer Protective Layer Material This embodiment provides a low-exudation buffer protective layer material.
[0077] 1000g of domestically produced inert macroporous styrene-divinylbenzene resin or hydrophilic-terminated macroporous resin was weighed and washed sequentially with ethanol, deionized water, 0.5mol / L hydrochloric acid, ultrapure water, 0.1mol / L sodium hydroxide, and ultrapure water. The resin was then added to 3L of 2wt% ethanolamine aqueous solution and treated at 50℃ for 4h to hydrophilically seal the residual active sites. It was then washed with ultrapure water until the conductivity of the effluent was below 10μS / cm. Finally, it was replaced sequentially with 25% ethylene glycol / water and 50% ethylene glycol / water, and pre-stabilized at 95℃ for 48h to obtain a low-precipitation buffer protective layer material.
[0078] The low-precipitation buffer protective layer material, after being immersed in 95°C and 50% ethylene glycol / water for 24 h, exhibited an effluent conductivity of 5.6 μS / cm, a TOC of 8.4 mg / L, and a Na+ content of... + K + Ca 2+ Mg 2+ The total amount precipitated is less than 0.2 mg / L.
[0079] Example 4: Preparation of a regenerable multi-stage synergistic pre-capture core capsule This embodiment provides a regenerative multi-stage cooperative pre-capture core capsule, the structural diagram of which is shown below. Figure 1 and Figure 2 A schematic diagram illustrating the staged capture mechanism of the high-valent metal capture layer and the divalent transition metal capture layer within the capture capsule is shown below. Figure 3 .
[0080] The pre-capture core capsule adopts a PPS porous cylindrical core capsule shell with an outer diameter of 72 mm and a length of 145 mm, and the effective filling volume of the core capsule is 0.42 L. PPS end caps are provided at both ends of the core capsule shell, and PPS support mesh and sealing rings are provided inside the end caps, so that the core capsule can be installed into or removed from the deionizer housing as a whole.
[0081] Along the coolant flow direction, the front capture core is sequentially configured with an inlet particle filter-distribution layer, a high-valence metal capture layer, a first PPS microporous baffle, a divalent transition metal capture layer, a second PPS microporous baffle, and a low precipitation buffer protection layer.
[0082] The inlet particulate filter-flow layer uses a combination of PPS fiber felt and PPS support mesh, with a thickness of 8 mm, accounting for approximately 5% of the effective volume of the core. The PPS fiber felt and PPS support mesh are not simply mixed, but rather arranged in a layered, sandwiched composite structure along the coolant flow direction. A three-layer sandwich structure is used: upstream PPS support mesh – downstream PPS support mesh. The ratio of the total thickness of the PPS fiber felt to the two layers of PPS support mesh is 4:1. The total thickness of the inlet particulate filter-flow layer is 8.0 mm, of which the PPS fiber felt is 6.4 mm thick, and the upstream and downstream PPS support meshes are each 0.8 mm thick, i.e., the ratio of the total thickness of the PPS fiber felt to the PPS support mesh is 4:1. The three layers are sequentially stacked and fixed by annular limiting grooves on the inner wall of the core and axial compression at the ends. No adhesives are used in the effective flow area, and resin particles are not mixed.
[0083] The low-precipitation high-valence metal capturing resin obtained in Example 1 was filled with a high-valence metal capturing layer, with a filling volume of 0.15 L, accounting for approximately 36% of the effective volume of the core capsule.
[0084] The first PPS microporous separator has a thickness of 2 mm, a pore size of 200 μm, and an open porosity of 48%.
[0085] The low-precipitation divalent transition metal capturing resin obtained in Example 2 was filled with a divalent transition metal capturing layer, with a filling volume of 0.18 L, accounting for approximately 43% of the effective volume of the core capsule.
[0086] The second PPS microporous separator has a thickness of 2 mm, a pore size of 200 μm, and an open porosity of 48%.
[0087] The low-precipitation buffer protective layer material obtained in Example 3 was filled with a volume of 0.06L, which accounts for about 14% of the effective volume of the core capsule.
[0088] After filling, the pre-capture core was flushed with 50% ethylene glycol / water solution for 5 core volumes and pre-stabilized at 95 °C for 24 h. The conductivity of the effluent after pre-stabilization was 9.2 μS / cm and the TOC was 13.6 mg / L.
[0089] Example 5: Glycol Coolant Deionizer for Fuel Cells Containing Renewable Pre-Capture Capsule This embodiment provides a fuel cell glycol coolant deionizer containing a regenerable multi-stage synergistic front-end capture core and a high-purity mixed-bed polishing layer at the rear end. See the structural diagram below. Figure 1 .
[0090] The deionizer includes a PPS+GF shell, a coolant inlet, a coolant outlet, the regenerable multi-stage synergistic pre-capture cartridge described in Example 4, a high-purity mixed-bed polishing layer, and an outlet high-temperature fine filter layer. The effective internal filling volume of the deionizer is 1.2L, of which the effective volume of the pre-capture cartridge is 0.42L, accounting for 35% of the effective internal filling volume; the high-purity mixed-bed polishing layer has a filling volume of 0.72L, accounting for 60% of the effective internal filling volume; and the outlet high-temperature fine filter layer and supporting structure account for approximately 5%.
[0091] The high-purity mixed-bed polishing layer is filled with a mixture of domestically produced high-purity H-type strong acid cation exchange resin and OH-type strong base anion exchange resin at a volume ratio of 45:55. The outlet high-temperature fine filtration layer uses PPS sintered filter sheets with a pore size of 60μm.
[0092] The simulated contaminated coolant was prepared by mixing ethylene glycol and ultrapure water at a mass ratio of 50:50, with an initial conductivity of 100±5 μS / cm, a pH of 7, and Fe... 3+ The initial concentration was 1.0 mg / L, Al 3+ The initial concentration was 1.0 mg / L, Cu 2+ The initial concentration was 0.8 mg / L, Zn 2+ The initial concentration was 0.8 mg / L, Na + The initial concentration was 2.0 mg / L, Cl - The initial concentration was 3.0 mg / L, SO4 2- The initial concentration was 3.0 mg / L. The test temperature was 95℃, and the circulation flow rate was 10 LPM.
[0093] Under the above conditions, the initial pressure drop of the deionizer in this embodiment was 12.8 kPa, the pressure drop was 14.6 kPa after 500 hours of operation, and the pressure drop was 16.8 kPa after 900 hours of operation. The initial outlet conductivity was 0.72 μS / cm, and the outlet conductivity remained below 5 μS / cm for the first 850 hours during operation.
[0094] In the evaluation of dynamic metal ion penetration, Fe in this embodiment 3+ Al 3+ Cu 2+ Zn 2+ The times to reach C / C0=0.10 were 405h, 426h, 785h, and 812h, respectively; the times to reach C / C0=0.50 were 518h, 540h, 940h, and 966h, respectively; and the times to reach C / C0=0.95 were 672h, 698h, 1165h, and 1194h, respectively. These results indicate that the regenerable multi-stage synergistic pre-capture core of this invention can preferentially capture high-valence metal ions and divalent transition metal ions, allowing the high-purity mixed-bed polishing layer at the back end to primarily perform residual ion removal and low-conductivity polishing functions.
[0095] Example 6: Acid washing and regeneration of the pre-capture core Run Example 5 to Fe 3+ And Al 3+ After achieving a C / C0 ratio of 0.10, the pre-capture core was removed and flushed with a 50% ethylene glycol-water mixture for three core volumes to remove residual coolant. Subsequently, a 0.5 mol / L hydrochloric acid solution was used as the acidic regeneration solution to flush four core volumes of the pre-capture core at a flow rate of 2 BV / h, causing the desorption of Fe, Al, Cu, Zn, and other metal ions from the high-valence metal capture layer and the divalent transition metal capture layer into the regeneration solution. Afterward, the core was flushed with ultrapure water until the conductivity of the effluent was below 20 μS / cm, followed by sequential replacement with 25% ethylene glycol-water and 50% ethylene glycol-water, and pre-stabilized at 95℃ for 12 h. (Flowchart shown). Figure 4 .
[0096] Measurements showed that the pre-capture core after the first regeneration had a significant effect on Fe. 3+ Al 3+ Cu 2+ Zn 2+ The dynamic capture capability remained at 94.2%, 93.5%, 95.1%, and 95.4% of the initial value, respectively; after the third regeneration, it remained at 88.6%, 87.9%, 90.8%, and 91.2%, respectively; and after the fifth regeneration, it remained at 81.4%, 80.7%, 84.6%, and 85.3%, respectively.
[0097] The results show that the regenerable multi-stage synergistic pre-capture core of the present invention can be regenerated multiple times through acid washing, and its metal ion capture capacity remains at a high level after 5 regenerations, making it suitable as a recyclable consumable unit for the ethylene glycol coolant deionizer of fuel cells.
[0098] Example 7: Determination of Composite Lifetime Based on Metal Ion Load / Outlet Conductivity / Voltage Drop This embodiment provides a method for determining the lifespan of a deionizer. See Figure 5 This is applicable to the ethylene glycol coolant deionizer of the fuel cell containing a regenerable pre-capture core as described in Example 5.
[0099] During vehicle or bench operation, the conductivity of the deionizer outlet coolant is periodically monitored. When the outlet conductivity is higher than 5 μS / cm for two consecutive measurements, the high-purity mixed bed polishing layer at the back end is deemed close to replacement requirements.
[0100] During the maintenance cycle, the pre-capture core is removed for small-volume acid washing diagnostics to detect the cumulative elution of Fe, Al, Cu, Zn, Ni, and Cr in the acid washing solution. When the cumulative elution reaches 70% of the theoretical metal capture capacity of the pre-capture core, it is determined that the pre-capture core has reached the regeneration condition.
[0101] Simultaneously monitor the pressure difference between the inlet and outlet of the deionizer. When the pressure difference between the inlet and outlet reaches 20 kPa or more at a flow rate of 10 LPM, or increases by more than 50% compared to the initial pressure drop, it is determined that there is a risk of blockage in the inlet particle filter / flow distribution layer or the pre-capture cartridge, requiring flushing, regeneration, or replacement.
[0102] When the front capture core reaches the regeneration condition, the outlet conductivity can still be lower than 5 μS / cm, indicating that the metal ion load determination can detect the front capture layer being close to saturation earlier than the outlet conductivity failure determination. When the back mixed bed reaches the replacement condition, the front capture core can still be used after regeneration, thus realizing the graded maintenance of front core regeneration and back mixed bed replacement.
[0103] Comparative Example 1: Deionizer using only high-purity mixed-bed resin This comparative example uses the same deionizer housing as Example 5, except that it does not have a regenerable multi-stage synergistic pre-capture core; instead, the deionizer is mainly filled with a high-purity strong acid cation / strong base anion mixed bed resin. Dynamic cycling evaluation was conducted using the same simulated contamination coolant and test conditions as in Example 5.
[0104] Under the above conditions, the initial pressure drop of the deionizer in this comparative example was 9.4 kPa, and the pressure drop was 11.2 kPa after 500 h of operation. The initial outlet conductivity was 0.68 μS / cm, but after 310 h of operation, the outlet conductivity increased to over 5 μS / cm.
[0105] The results of the metal ion penetration evaluation showed that Fe 3+ Al 3+ Cu 2+ Zn 2+ The times to reach C / C0=0.10 were 59h, 65h, 132h, and 143h, respectively; the times to reach C / C0=0.50 were 90h, 98h, 205h, and 220h, respectively. These results indicate that, without a pre-capture core, the high-purity mixed-bed resin directly bears the entire load of metal ions and residual ions, resulting in earlier metal ion penetration and a shorter low-conductivity maintenance lifespan.
[0106] Comparative Example 2: Single-layer commercial IDA chelating resin + mixed-bed deionizer This comparative example uses the same deionizer housing as Example 5, except that only a commercial IDA chelating resin layer is provided on the inlet side, without the multi-stage core structure of a high-valence metal capture layer, a divalent transition metal capture layer, and a low-precipitation buffer protection layer. The commercial IDA chelating resin filling volume is 0.42 L, and the high-purity mixed-bed resin filling volume is 0.72 L.
[0107] Under the same test conditions as in Example 5, the initial outlet conductivity of this comparative example was 1.35 μS / cm, and after 470 h of operation, the outlet conductivity increased to over 5 μS / cm. 3+ Al 3+ Cu 2+ Zn 2+ The times to reach C / C0=0.10 were 128h, 140h, 286h and 304h respectively; the times to reach C / C0=0.50 were 182h, 198h, 392h and 418h respectively.
[0108] This result indicates that monolayer commercial IDA chelating resins are effective against Cu. 2+ Zn 2+ Divalent metal ions have a certain ability to capture them, but not Fe. 3+ Al 3+ Commercial resins that do not undergo low-precipitation treatment may have insufficient capture capacity for high-valence metal ions and may have high initial outlet conductivity.
[0109] Comparative Example 3: Disordered mixing and packing of high-valence metal trapping layers and divalent transition metal trapping layers. This comparative example uses the same deionizer housing and the same type of resin material as Example 5. The difference is that the high-valence metal capturing resin obtained in Example 1, the divalent transition metal capturing resin obtained in Example 2, and the low precipitation buffer material obtained in Example 3 are randomly mixed and directly filled into the front end region. The first microporous partition, the second microporous partition, and the sequential layered structure are not set.
[0110] Under the same test conditions as in Example 5, this comparative example Fe 3+ Al 3+ Cu 2+ Zn 2+ The times to reach C / C0=0.10 were 312h, 326h, 650h, and 672h, respectively; the times to reach C / C0=0.50 were 410h, 428h, 805h, and 824h, respectively. The initial pressure drop was 13.6kPa, and the pressure drop was 17.5kPa after 500h of operation.
[0111] The results show that, when the resin materials are the same but the hierarchical flow structure is lacking, the high-valence metal capture resin and the divalent metal capture resin cannot fully utilize the hierarchical capture advantage according to the flow direction, and disordered mixing may lead to local short-flow and resin layer compaction, and the metal ion penetration time is shorter than that of Example 5 of the present invention.
[0112] A comparison of metal ion penetration curves for different deionizer systems in coolants contaminated with Fe, Al, Cu, and Zn composite pollutants is shown in the figure. Figure 6 .
[0113] Comparative Example 4: Pre-capture core without a low-deposition buffer protection layer This comparative example uses the same front capture core structure as Example 5, except that the low precipitation buffer protection layer is removed, so that the rear end of the divalent transition metal capture layer is directly adjacent to the high-purity mixed bed polishing layer.
[0114] Under the same test conditions as in Example 5, the initial outlet conductivity of this comparative example was 1.18 μS / cm, and the TOC of the effluent was 22.4 mg / L in the first 24 hours of operation; the initial outlet conductivity of Example 5 was 0.72 μS / cm, and the TOC of the effluent was 13.6 mg / L in the first 24 hours of operation. After 700 hours of operation, the front end of the high-purity mixed-bed polishing layer in this comparative example showed a more obvious color change and local compaction, and the fluctuation range of the outlet conductivity was higher than that in Example 5. This result indicates that the low-precipitation buffer protective layer can reduce the impact of front-end modified resin precipitates, resin powder, and local ion impacts on the back-end high-purity mixed-bed polishing layer, which helps to improve the operational stability of the deionizer.
[0115] As shown in Example 5 and Comparative Examples 1-3, the regenerable multi-stage synergistic pre-capture core + post-high-purity mixed-bed polishing system of the present invention exhibits a longer dynamic penetration time for coolants contaminated with Fe, Al, Cu, and Zn composites. With C / CO = 0.10 as the initial penetration determination point, the Fe in Example 5 of the present invention... 3+ Al 3+ Cu 2+ Zn 2+ The breakthrough times were 405h, 426h, 785h and 812h, respectively, all significantly later than the systems using only high-purity mixed bed resin, single-layer commercial IDA chelating resin + mixed bed, and disordered mixed filling resin.
[0116] Compared to Comparative Example 1, which used only high-purity mixed-bed resin, the Fe in Example 5 of this invention... 3+ Al 3+ Cu 2+ Zn 2+ The initial breakthrough time was extended by approximately 5.86 times, 5.55 times, 4.95 times, and 4.68 times, respectively. Compared with a single-layer commercial IDA chelating resin + mixed bed system, the Fe in Example 5 of this invention... 3+ Al 3+ Cu 2+ Zn 2+ The initial penetration time was extended by approximately 2.16 times, 2.04 times, 1.74 times, and 1.67 times, respectively. Compared with the disordered mixed packing system, the Fe in Example 5 of this invention... 3+ Al 3+ Cu 2+ Zn 2+ The initial penetration time was extended by approximately 29.8%, 30.7%, 20.8%, and 20.8%, respectively.
[0117] As can be seen from Example 6, after five acid washing and regeneration processes, the pre-capture core of the present invention effectively captures Fe... 3+ Al 3+ Cu 2+ Zn 2+ The capture capabilities remained at 81.4%, 80.7%, 84.6%, and 85.3% of their initial values, respectively, indicating that the pre-capture core has good regeneration and reuse performance.
[0118] As can be seen from Example 7, the composite life determination method for metal ion load / outlet conductivity / voltage drop established by the present invention can distinguish the timing of regeneration of the front capture core, the timing of replacement of the rear mixed bed and the risk of filter blockage, which is beneficial to the after-sales maintenance of fuel cell vehicles and the management of deionizer consumables.
[0119] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0120] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0121] In the foregoing description of this specification, references to terms such as "one embodiment," "another embodiment," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment is included in at least one embodiment of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples, without contradiction. Additionally, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features.
[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A pre-capture capsule for ethylene glycol coolant in a fuel cell, characterized in that, The pre-capture core is disposed on the coolant inlet side of the deionizer. The pre-capture core includes, in sequence along the coolant flow direction, an inlet particle filter-distribution layer, a high-valence metal capture layer, a first microporous baffle, a divalent transition metal capture layer, a second microporous baffle, and a low-deposition buffer protection layer. The high-valence metal trapping layer comprises a first low-precipitation chelating resin containing at least one phosphonic acid group, an aminophosphonic acid group, or a hydroxamic acid group; The divalent transition metal trapping layer includes a second low-precipitation chelating resin containing at least one iminodiacetic acid group or an aminocarboxylic acid group.
2. The pre-capture core capsule according to claim 1, characterized in that, The first low-precipitation chelating resin uses macroporous styrene-divinylbenzene resin, chloromethylated styrene-divinylbenzene resin, epoxy-based macroporous resin, amination-based macroporous resin, or a weakly basic macroporous resin that can be modified secondaryly as a matrix, and introduces at least one phosphonic acid group, aminophosphonic acid group, or phosphonic acid group through phosphonomethylation, hydroxamic acidation, or aminophosphonohydrination reactions; and / or, The second low-precipitation chelating resin uses macroporous styrene-divinylbenzene resin, chloromethylated styrene-divinylbenzene resin, epoxy macroporous resin, amino-modified macroporous resin or weakly basic macroporous resin that can be modified twice as a matrix, and introduces iminodiacetic acid groups and / or aminocarboxylic acid groups through at least one of iminodiacetic acid grafting or aminocarboxylic acid grafting.
3. The pre-capture core capsule according to claim 1, characterized in that, The volume ratio of the high-valent metal trapping layer to the divalent transition metal trapping layer is 10:90 to 90:10; and / or, The inlet particle filter-distribution layer occupies 3-15% of the effective volume of the pre-capture core; and / or, The high-valence metal trapping layer occupies 20-50% of the effective volume of the front trapping core; and / or, The divalent transition metal trapping layer occupies 25-55% of the effective volume of the pre-trapping core; and / or, The low-deposition buffer protective layer occupies 5-20% of the effective volume of the pre-capture core.
4. The pre-capture core capsule according to claim 1, characterized in that, The low-precipitation buffer protective layer comprises at least one of the following: hydrophilic end-capped macroporous resin treated with low precipitation, inert macroporous resin, low-precipitation weak acid resin, low-precipitation weak base resin, PPS supporting particles, PTFE supporting particles, and PES supporting particles; and / or, The first and second microporous partitions are each independently selected from at least one of PPS microporous partitions, PPS support mesh, PTFE support mesh, PEEK microporous partitions, and PVDF microporous partitions; and / or, The pore sizes of the first and second microporous separators are 50~500μm, respectively; The open area ratios are 30% to 70%.
5. The pre-capture core capsule according to claim 1, characterized in that, The pre-capture core includes a detachable core, a pull-out core, a replaceable inner liner, a recyclable resin pack, a perforated cylindrical resin core, or a pouch-type resin core.
6. A method for preparing a pre-capture core capsule according to any one of claims 1 to 5, characterized in that, Includes the following steps: The inlet particle filter-distribution layer, the high-valence metal capture layer, the first microporous partition, the divalent transition metal capture layer, the second microporous partition, and the low precipitation buffer protection layer are sequentially filled into the core capsule shell or core capsule bag. The filled core capsule was subjected to ethylene glycol-water replacement and pre-stabilization treatment to obtain a regenerable multi-stage synergistic pre-capture core capsule.
7. A deionizer, characterized in that, The deionizer includes a housing, a coolant inlet, a coolant outlet, a pre-capture core as described in any one of claims 1 to 5, and a high-purity mixed-bed polishing layer disposed at the rear end of the pre-capture core. The coolant flows sequentially through the coolant inlet, the capture core, the high-purity mixed bed polishing layer, and the coolant outlet.
8. The deionizer according to claim 7, characterized in that, The pre-capture core occupies 15-60% of the effective filling volume inside the deionizer; the high-purity mixed-bed polishing layer occupies 40-85% of the effective filling volume inside the deionizer; and / or, The high-purity mixed-bed polishing layer comprises H-type strong acid cation exchange resin and OH-type strong base anion exchange resin; and / or The deionizer further includes an outlet high-temperature fine filtration layer disposed at the rear end of the high-purity mixed bed polishing layer, wherein the outlet high-temperature fine filtration layer is a PPS sintered filter, PPS fiber felt, PTFE filter, PES filter, glass fiber filter, or a combination thereof; and / or, The housing is at least one of PPS, PPS and fiberglass, PPA, PEEK, PA66 and fiberglass, aluminum alloy inner lining insulation layer, or stainless steel inner lining insulation layer; and / or The deionizer has an initial pressure drop of ≤20 kPa at a coolant flow rate of 10 LPM; and an outlet coolant conductivity of ≤5 μS / cm.
9. A fuel cell, characterized in that, The fuel cell's coolant circulation system is provided with a pre-capture capsule as described in any one of claims 1 to 5 or a deionizer as described in any one of claims 7 to 8.
10. An electrochemical energy conversion device, characterized in that, The electrochemical energy conversion device is provided with a pre-capture capsule as described in any one of claims 1 to 5 or a deionizer as described in any one of claims 7 to 8 in its coolant circulation system, or the electrochemical energy conversion device includes a fuel cell as described in claim 9.